Pain Perception in Phacoemulsification with Topical Anesthesia and Evaluation of Factors Related with Pain - Dadacı, Zeynep (Turk J Ophthalmol, 2016)
OBJECTIVES: Evaluation of pain during and after phacoemulsification with topical anesthesia in patients with senile cataract and investigation of factors related with pain. MATERIALS AND METHODS: Ninety-two adult patients scheduled for routine clear corneal phacoemulsification with topical anesthesia who had no previous cataract surgery in their fellow eyes were included in the study. Verbal pain scale and visual analog scale were used to measure pain intensity. Demographic characteristics, concomitant systemic diseases, drug consumption, need of additional anesthesia during surgery, surgical complications, duration of surgery and surgeon comfort were also evaluated for each patient. RESULTS: Seventy-two patients (78.3%) reported pain during surgery and 68 patients (73.9%) reported pain in the period after the surgery. When the intensity of pain during the surgery was evaluated, the percentage of patients reporting mild, moderate and intense pain was 35.9%, 25.0% and 17.4%, respectively. The average verbal pain score during the surgery was 1.4±1.0 (0-3). Reported pain level was not associated with age or gender (p>0.05). Diabetic patients and patients who consumed nonsteroidal anti-inflammatory drugs in the morning before operation reported less pain during and after the surgery (p<0.05). There were no complications except posterior capsule rupture in one patient. Duration of surgery was longer in patients who reported pain during surgery (p<0.05). There was no significant difference between pain reported during surgery and surgeon comfort (p>0.05). CONCLUSION: Patients frequently experience pain during phacoemulsification with topical anesthesia. Although pain perception does not affect surgical success, preoperative administration of analgesics in suitable patients or giving additional anesthesia to patients reporting severe pain during surgery may increase patient comfort.